Accuracy of Retinopathy of Prematurity Diagnosis by Retinal Fellows - Chan, R. V. Paul (2010)
PURPOSE: To measure the accuracy of retinopathy of prematurity (ROP) diagnosis by retinal fellows. METHODS: An atlas of 804 retinal images was captured from 248 eyes of 67 premature infants with a wide-angle camera (RetCam-II; Clarity Medical Systems, Pleasanton, CA). Images were uploaded to a study website, from which an expert pediatric retinal specialist and seven retinal fellows independently provided a diagnosis (no ROP, mild ROP, type-2 ROP, or treatment-requiring ROP) for each eye. Sensitivity and specificity of each retinal fellow was calculated, compared to a reference standard of diagnosis by the expert pediatric retinal specialist. RESULTS: For detection of type-2 or worse ROP by fellows, mean (range) sensitivity was 0.751 (0.512–0.953) and specificity was 0.841 (0.707–0.976). For detection of treatment-requiring ROP, mean (range) sensitivity was 0.914 (0.667–1.000) and specificity was 0.871 (0.678–0.987). CONCLUSIONS: In general, fellows demonstrated high accuracy for detecting ROP. However, 3/7 fellows achieved less than 80% sensitivity for diagnosis of type-2 or worse ROP, and 2/7 achieved less than 90% sensitivity for diagnosis of treatment-requiring ROP. This could lead to under-management and under-treatment of clinically significant disease, and raises potential concerns about the quality of ROP screening performed by less experienced examiners.